MORAL SEKS DALAM CERITA PEWAYANGAN - Rahno Triyogo (Institut Seni Indonesia Surakarta, 2010)
Sex (intercourse) represents a relation of two personalities that is between a husband and a wife involving physic, feeling, emotion, and the soul based on love and mutual respect. Sex that is executed by unmarried couple is supposed to be adultery sin and immoral in some religions as well as cultures. Each culture against the adultery so that people who does the adultery will get a heavy moral sanction. The moral sanction means the fall of the man’s dignity as a cultured human being. Key words: sex (intercourse), moral, dignity